ANALISIS EVALUASI MANAJEMEN PARIWISATA HALAL PERSPEKTIF FATWA DSN-MUI No.108/DSN-MUI/X/2016 : (Studi Atas Destinasi Wisata di Kabupaten Bantul, Yogyakarta) - Hakim, Muhammad Rukhiyatul; Ismiati, Baiq (DAS Institute, 2024)
As a Muslim-majority country, Indonesia recognizes that Islamic principles cover various aspects of life, including economics and industrial management. One sector that is experiencing rapid growth is halal tourism, which has great potential to continue to grow. This study aims to evaluate the extent to which tourist destinations in Bantul Regency meet halal standards regulated in Fatwa DSN MUI No.108/DSN-MUI/X/2016 concerning Tourism Implementation Guidelines in accordance with Sharia Principles. The research method used is qualitative with a descriptive analysis approach through case studies, involving data collection from various tourist destinations in Bantul Regency. The analysis results show that the compatibility level between implementing tourist destinations in Bantul Regency and the parameters of halal destinations based on Fatwa DSN MUI No.108 / DSN-MUI / X / 2016 is 93.94%. Nevertheless, there is still room for improvement, especially related to practices contrary to the principles of religious law, especially in tourist destinations that have links to culture, history, or places considered sacred. This is in line with the tendency of Indonesian society, especially Javanese, which tends to have mystical and supernatural views.